Quadriceps Strength Influences Patient Function More Than Single Leg Forward Hop During Late-Stage ACL Rehabilitation - Meredith Chaput; Marcus Palimenio; Brooke Farmer; Dimitrios Katsavelis; Jennifer J. Bagwell; Kimberly A. Turman; Chris Wichman; Terry L. Grindstaff (North American Sports Medicine Institute, 2021)
# Background A comprehensive battery of tests are used to inform return to play decisions following anterior cruciate ligament (ACL) reconstruction. Performance measures contribute to patient function, but it is not clear if achieving symmetrical performance on strength and hop tests is sufficient or if a patient also needs to meet minimum unilateral thresholds. # Hypothesis/Purpose To determine the association of quadriceps strength and single-leg forward hop performance with patient-reported function, as measured by the IKDC Subjective Knee Form (IKDC), during late-stage ACL rehabilitation. A secondary purpose was to determine which clinical tests were the most difficult for participants to pass. # Study Design Descriptive Laboratory Study # Methods Forty-eight individuals with a history of ACL-R (32 female, 16 male; mean±SD age=18.0±2.7 y; height=172.4±7.6 cm; mass=69.6±11.4 kg; time since surgery=7.7±1.8 months; IKDC=86.8±10.6) completed the IKDC survey, quadriceps isometric strength, and single-leg forward hop performance. The relationship between IKDC scores and performance measures (LSI and involved limb) was determined using stepwise linear regression. Frequency counts were used to determine whether participants met clinical thresholds (IKDC $≥$ 90%, quadriceps and single-leg forward hop LSI $≥$ 90%, quadriceps peak torque $≥$ 3.0 Nm/kg, and single-leg forward hop $≥$ 80% height for females and $≥$ 90% height for males). # Results Quadriceps LSI and involved limb peak torque explained 39% of the variance in IKDC scores while measures of single-leg forward hop performance did not add to the predictive model. Nearly 90% of participants could not meet established clinical thresholds on all five tests and quadriceps strength (LSI and peak torque) was the most common unmet criteria (71% of participants). # Conclusions During late-stage ACL rehabilitation deficits in quadriceps strength contribute more to patient function and are greater in magnitude compared to hop test performance. # Level of evidence Cross-Sectional Study, Level 3